2001
DOI: 10.1007/bf02463915
|View full text |Cite
|
Sign up to set email alerts
|

Alternation of nuclear phase in the filamentous basidiomycete, Helicobasidium mompa

Abstract: Variation in the number of nuclei and cellular ploidy were observed in eight strains of Helicobasidium mompa. The basidiospores, single-spore isolates and field-isolated strains were all dikaryons. The cellular ploidy, which was assessed by analyzing the fluorescence emitted by DAPI-stained nuclei, was unstable: monokaryotic strains derived from the original dikaryotic strains by successive subcultures were mainly tetraploid, although the original dikaryon was in most cases diploid. On the other hand, a dikary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Because the RDRP gene is indispensable in viral replication (Ghabrial 1998), we used strain V70 as a dsRNA donor and investigated the transmission of dsRNA-1 between strains of H. mompa. Karyotypes of two strains, V1M and V3M, were already reported as monokaryotic (Aimi et al 2001), and we reconfirmed that these strains were monokaryotic before the experiment.…”
Section: Strains Of Helicobasidium Mompasupporting
confidence: 88%
See 3 more Smart Citations
“…Because the RDRP gene is indispensable in viral replication (Ghabrial 1998), we used strain V70 as a dsRNA donor and investigated the transmission of dsRNA-1 between strains of H. mompa. Karyotypes of two strains, V1M and V3M, were already reported as monokaryotic (Aimi et al 2001), and we reconfirmed that these strains were monokaryotic before the experiment.…”
Section: Strains Of Helicobasidium Mompasupporting
confidence: 88%
“…We speculate this is due to the monokaryotic state of H. mompa. Aimi et al (2001) reported that the diploid dikaryon seems to be a normal nuclear phase of H. mompa in nature. They also attributed monokaryotization in H. mompa to the fusion of two nuclei and the unstableness of cellular ploidy in this fungus to either a lack of or a defect in mating-type factors.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although the two monokaryotic strains were thought to be the same or closely related (Suzaki et al 2003), HmTV1-17 virus seemed to be transmitted from these monokaryotic strains into different MCGs randomly (Table 2). Aimi et al (2001) reported that the karyotype of H. mompa was variable and that monokaryotic strains of H. mompa resulted from nuclear fusion in dikaryotic strains. Mating-type factors of basidiomycetous fungi were associated with maintenance of the dikaryotic phase (Casselton and Olesnicky 1998), and Raper and Raper (1973) reported that defects in mating-type factors in the basidiomycete Schizophyllum commune affected self-nonself recognition between the fungal isolates.…”
Section: Discussionmentioning
confidence: 98%